2022
DOI: 10.1101/2022.04.28.489561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ST6GAL1 sialyltransferase promotes acinar to ductal metaplasia and pancreatic cancer progression

Abstract: The role of aberrant glycosylation in pancreatic ductal adenocarcinoma (PDAC) remains an under-investigated area of research. In this study, we determined that the ST6GAL1 sialyltransferase, which adds α2,6-linked sialic acids to N-glycosylated proteins, is upregulated in patients with early-stage PDAC, and further increased in advanced disease. A tumor-promoting function for ST6GAL1 was elucidated using tumor xenograft models with human PDAC cells. Additionally, we developed a genetically-engineered mouse (GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, the up-miR, miR-221-5p, which has a strong impact on ST6GAL1 and α-2,6-sialylation, is highly expressed in pancreatic cancer and is associated with decreased survival . In recent work, ST6GAL1 and α-2,6-sialylation have also been shown to be important in pancreatic cancer formation and progression and correlate with decreased survival. ,, This points toward a potential functional role for upregulatory miRNA in controlling cancer-related protein and glycan expression.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, the up-miR, miR-221-5p, which has a strong impact on ST6GAL1 and α-2,6-sialylation, is highly expressed in pancreatic cancer and is associated with decreased survival . In recent work, ST6GAL1 and α-2,6-sialylation have also been shown to be important in pancreatic cancer formation and progression and correlate with decreased survival. ,, This points toward a potential functional role for upregulatory miRNA in controlling cancer-related protein and glycan expression.…”
Section: Resultsmentioning
confidence: 96%
“… 34 In recent work, ST6GAL1 and α-2,6-sialylation have also been shown to be important in pancreatic cancer formation and progression and correlate with decreased survival. 5 , 6 , 38 This points toward a potential functional role for upregulatory miRNA in controlling cancer-related protein and glycan expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated Wnt signaling, including via increased expression of regulators like WNT3A and β-catenin, was identified in RNAsequencing analysis of metastatic subclones of pancreatic cancer cell lines S2-LM7AA and S2-013 that expressed high levels of ST6Gal1 (Britain et al, 2021). This finding was recently corroborated with RNA-sequencing analysis of the pancreas from GEMM models with pancreas-specific ST6Gal1 overexpression (Chakraborty et al, 2022): these data showed elevated stem cell-related pathways including Wnt (Chakraborty et al, 2022). Furthermore, elevated levels of ST6Gal1 in the colorectal cancer cell lines Caco-2 and SW48 were associated with increased expression of WNT3a and β-catenin as well as fluorouracil (5-FU) resistance (Cui et al, 2018).…”
Section: Wnt Signalingmentioning
confidence: 73%
“…This led to delayed disease development and progression (Kurz et al, 2021). Corroborating these findings, in pancreatic organoids developed from mice expressing K-Ras G12D under the control of Pdx1-Cre, knockdown of ST6Gal1 inhibited organoid growth (Chakraborty et al, 2022). Considering RAS mutations are observed in up to 93% of pancreatic cancer patients, the results of these studies strongly suggest ST6Gal1 as a downstream mediator of, and potential therapeutic target in, RASmediated pancreatic oncogenesis.…”
Section: Ras Signalingmentioning
confidence: 88%